Association between pulp stones and systemic diseases: A case-control study - Romano, Bruna de Souza; Kublitski, Prescila Mota de Oliveira; Juglair, Mariana Martins; Brancher, João Armando; Baratto-Filho, Flares; Michel-Crosato, Edgard; Gabardo, Marilisa Carneiro Leão (ABCS Health Sciences, 2024)
Introduction: Pulp stones (PS) are calcifications commonly found in the pulp tissue that may be associated with systemic diseases. Objective: To evaluate the association between PS and systemic diseases. Methods: A case-control study with the inclusion of individuals from 18 to 65 years of age, of both sexes. Analysis was made of 1047 digital panoramic radiographs. The controls could not have any teeth with PS; the cases were the contrary. A questionnaire comprising demographic, habit, and general health (diabetes, problems with blood vessels, altered cholesterol level, heart attack, kidney or gallbladder stone, arthritis, or autoimmune disease, and for women, endometriosis, and ovarian cyst). Data were submitted to the Student's t-test to identify differences between groups about sex and age. The Chi-square test was applied to the cross-tabulation. The analyses were performed using SPSS®, version 25.0, with a 5% significance level. Results: 490 patients participated (242 cases and 248 controls). There was no difference between groups for the sex (p=0.966) and age (p=0.186). Only “kidney stone” was associated with the case group (p=0.001), being almost three times higher when compared to the control group. No significant differences were found in females about the presence or absence of PS (p>0.05). Conclusion: In this research, it is suggested the existence of an association between kidney stones and the presence of pulp stones.